Determinants of Audit Quality in the Digital Era: The Influence of Audit Tenure, Artificial Intelligence, and Firm Complexity - Kadua, Nada Cantika Putri (PT. Anagata Sembagi Education, 2026)
The rapid development of digital technology has transformed the auditing environment, influencing the determinants of audit quality in modern organizations. The integration of digital systems, advanced data analytics, and Artificial Intelligence (AI) has changed how auditors collect, analyze, and evaluate financial information. Alongside these technological developments, traditional factors such as audit tenure and firm complexity continue to play important roles in shaping audit outcomes. This study aims to examine the influence of audit tenure, Artificial Intelligence adoption, and firm complexity on audit quality in the digital era. This research employs a quantitative approach using secondary data obtained from audited annual reports and financial statements of publicly listed companies. The sample was selected using purposive sampling, and the collected data were analyzed using multiple linear regression analysis to examine the relationships between the independent variables and audit quality. The results indicate that audit tenure and Artificial Intelligence adoption have a positive and significant effect on audit quality, suggesting that longer auditor–client relationships improve auditors’ understanding of client operations while AI enhances the efficiency and accuracy of audit procedures. Meanwhile, firm complexity does not have a significant effect on audit quality, indicating that auditors are generally capable of managing complex organizational structures through standardized audit practices and technological support. The study concludes that the transformation of the audit environment in the digital era has shifted the determinants of audit quality toward a combination of professional experience and technological capability, highlighting the strategic role of Artificial Intelligence in improving modern audit practices.